Delayed Management of a Button Battery Foreign Body in the Esophagus: A Case Report - Mizwar Mizwar; Ade Asyari (Jurnal Ilmu Kesehatan Indonesia)
Introduction: A Foreign body ingestion and ofreign body aspiration commonly affect children between 6 months and 6 years. Items that are commonly swallowed by children are small and shiny object, such button batteries and magnets that have increased rapidly over the last decade. Botton battery ingestion an established surgical emergency, requiring immediate removal. Delay in diagnosis can lead possible complication such as inflammation, necrosis of esophageal mucosa and esophageal perforation. Rigid esophagoscopy is mainstay procedure of management foreign body in esophagus.